Pelatihan Pot Gardening sebagai Upaya Meningkatkan Literasi Lingkungan Siswa di Sekolah Dasar - Affia Nuraihanum; M Choirul Muchlis; Vradinta Halizanindya; Almina Kusaniyah (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2025)
The global challenges caused by climate change and environmental degradation demand a collective response from all levels of society, especially among the younger generation. A lack of understanding of environmental issues often leads to environmentally unfriendly behavior, so an effective and engaging educational approach is needed. Community service activities have an impact on increasing environmental literacy of students at SD N 2 Padureso through pot gardening training.. This training not only introduces the basic practices of container gardening but also holistically integrates concepts of ecology, recycling, and conservation. The goal of this program is to shift students’ perspectives from being mere observers to active participants in maintaining environmental sustainability. The method used in this community service activity is Participatory Action Research (PAR), which allows students to become active subjects in the learning process. The training results showed significant changes in students’ understanding and behavior regarding environmental issues. Previously, many students were unaware of the importance of recycling and water conservation, but after the training, there was a noticeable shift in their perspectives and actions. This community service activity demonstrates that educational-practical approaches, such as pot gardening through the PAR method, are highly effective in enhancing students’ environmental literacy, with a focus on concrete actions and active participation. Thus, students not only become observers but also agents of change who care about their surrounding environment.